Modeling Indonesia’s Inflation Based on E-Money Transaction Volume with Local Polynomial Estimator Approach - Purwoko, Chaerobby Fachri Fauzan; Farida, Putri Nur; Ramadhani, Sefanny Nur; Erson, Vianda Mutiarani (Interdisciplinary Social Studies, 2022)
Background: The volume of electronic money transactions in Indonesia tends to fluctuate, before finally experiencing a decrease at the beginning of the Covid-19 pandemic and reaching the lowest level in May 2020 which then slowly increased again until September 2021. Bank Indonesia (BI) with the government and relevant authorities cooperated in taking steps to monitor, assess, and mitigate the impact of the spread of the Covid-19 virus. Aim: This study aims to find out how the variable effect of electronic money transaction volume (e-money) influences inflation in Indonesia and how accurate the prediction of the volume of electronic money transactions in the future Method: The method used in this research is a quantitative research method with an associative type of research approach. This study uses a type of secondary data involving a quantitative variable where data in the form of Time series that takes the object of the State of Indonesia as a reference. Data involves a single quantitative predictor variable. Findings: Based on this study, the authors found that there needs to be an increase in the volume of electronic transactions by 484,630,000 to increase inflation to reach the target in 2021.